Persistent Postural-Perceptual Dizziness - Staab, Jeffrey P. (Seminars in Neurology, 2020)
Persistent postural-perceptual dizziness (PPPD) was defined for the International Classification of Vestibular Disorders in 2017. It is a chronic vestibular disorder that manifests with waxing and waning symptoms of dizziness, unsteadiness, or nonspinning vertigo that last for 3 months or more and are exacerbated by upright posture, active or passive motion of self, and exposure to environments with complex or moving visual stimuli. Triggers of PPPD include a wide variety of conditions that may cause vestibular symptoms or disrupt balance functioning, including neuro-otologic and other medical conditions and psychological distress. The diagnosis is made by identifying key symptoms in patients' histories and conducting physical examinations and diagnostic testing of sufficient detail to establish PPPD as opposed to other illnesses. Ongoing research is providing insights into the pathophysiological mechanisms underlying PPPD and support for multimodality treatment plans incorporating specially adapted vestibular rehabilitation, serotonergic medications, and cognitive-behavior therapy.
Keywords: chronic dizziness; visual dependence; postural control; neurologic disorder